HER3 Differentiates Basal From Claudin Type Triple Negative Breast Cancer and Contributes to Drug and Microenvironmental Induced Resistance - Sinevici, Nicoleta; Ataeinia, Bahar; Zehnder, Veronica; Lin, Kevin; Grove, Lauren; Heidari, Pedram; Mahmood, Umar (Frontiers in Oncology, 2020)
Triple Negative Breast Cancer (TNBC) is an aggressive form of Breast Cancer (BC). Numerous kinase inhibitors (KI) targeting different pathway nodes have shown limited benefit in the clinical setting. In this study, we aim to characterize the extent of HER3 reliance and to define the effect of Neuregulin (NRG) isoforms in TNBCs. Basal and Claudin type TNBC cell lines were treated with a range of small molecule inhibitors, in the presence or absence of the HER3 ligand NRG. Single agent and combination therapy was also evaluated in human cancer cell lines through viability and biochemical assessment of the AKT/MAPK signaling pathway. We show that Basal (BT20, HCC-70 and MDA-MB-468) and Claudin type (MDA-MB-231, BT-549) TNBC cell lines displayed differential reliance on the HER family of receptors. Expression and dynamic HER3 upregulation was predominant in the Basal TNBC subtype. Furthermore, the presence of the natural ligand NRG showed potent signalling through the HER3-AKT pathway, significantly diminishing the efficacy of the AKT and PI3K inhibitors tested. We report that NRG augments the HER3 feedback mechanism for continued cell survival in TNBC. We demonstrate that combination strategies to effectively block the EGFR-HER3-AKT pathway are necessary to overcome compensatory mechanisms to NRG dependent and independent resistance mechanisms. Our findings suggests that the EGFR-HER3 heterodimer forms a major signalling hub and is a key player in tumorigenesis in Basal but not Claudin type TNBC tested. Thus, HER3 could potentially serve as a biomarker for identifying patients in which targeted therapy against the EGFR-HER3-AKT axis would be most valuable.